If the above equation is true for all real and , what is the number of values can take?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Firstly we prove injectivity.
If f ( a ) = f ( b ) ,
f ( f ( f ( a ) ) + y ) − f ( f ( a ) ) = f ( f ( y ) ) + a and f ( f ( f ( b ) ) + y ) − f ( f ( b ) ) = f ( f ( y ) ) + b
But the LHSs are the same so
f ( f ( y ) ) + a = f ( f ( y ) ) + b ⇒ a = b
Now set x = 0 .
This gives
f ( y + c ) = f ( f ( y ) ) ⇒ f ( y ) = y + c ∀ y ∈ R
where c = f ( f ( 0 ) )
The conclusion follows from here.